Cultivating Civic Ecology: A Photovoice Study with Urban Gardeners in Lisbon, Portugal. Issue 1 (1st March 2016) - Harper, Krista; Afonso, Ana Isabel
Abstract : Urban gardens are a form of self-provisioning, leisure and activist practice that is cropping up in cities around the world (Mougeot 2010). We present the history and contemporary terrain of Lisbon's urban gardens and discuss the cultural values that gardeners attach to the practice of growing food in interstitial urban spaces. We present initial findings from our research with an urban gardeners' association as it attempts to transform informal or clandestine garden spaces into an 'urban agricultural park'. This coalition of gardeners from diverse socioeconomic and ethnic backgrounds is reclaiming land and using a participatory design process to create a shared space. They hope to grow vegetables and to re-grow 'community' by forging shared experiences in the neighbourhood. We describe how we used Photovoice as a process for exploring residents' motivations in planting informal and community gardens on public land. What visions of sustainability and the contemporary city emerge from the practice of urban gardening? What kinds of urban gardening practices produce 'communities of practice' that cross ethnic, socioeconomic, and generational lines? The Photovoice approach allowed us to examine how gardeners conceptualise their use of urban space as they build new civic identities around gardening and make political claims to gain access and control over vacant land.